FRI0183 Long-term survival of tumor necrosis factor-alpha inhibitor therapies in a spanish cohort of rheumatoid arthritis patients. (23rd January 2014) - Caliz, R.; Ferrer, MA; Soto, MJ; Garcia, A; Utrilla, A; Salas, P; Lopez-Sidro, M; Romani, L; Acevedo, Z; Notario, I; Sainz, J; Cáliz, R.; et al.
Abstract : Background: Several European studies have proven differences in long-term survival among the different anti-TNF treatments. These differences have been observed in our clinical practice. Objectives: To investigate the safety and survival rate of tumor necrosis factor (TNF) α inhibitors Infliximab (INF), Adalimumab (ADA) and Etanercept (ETA) in patients with rheumatoid arthritis (RA). Methods: Observational, retrospective study performed on RA patients treated with TNF-α inhibitors and followed between 2005 and 2011 in our hospital. Safety data were obtained analyzing the causes of discontinuations of treatment due to any causes or adverse events at 1, 2 and 5 years. Survival rates were assessed at 1, 2 and 5 years. Kaplan-Meier survival analysis was performed. Discontinuation from anti-TNF-α due to any cause was defined as final event. Results: 297 patients were included, 246 are female (77.6%), with a mean age of 45 years: 85 (28.61%) patients received INF, 73 (24.57%) ETA and 139 (46.80%) ADA, which have been treated with DMARDs (46.4% Mtx; 42.9 leflunomide, 10.1% sulphasalazine). Patients treated with anti-TNF had no significant differences in the baseline HAQ and DAS-28. TNF-α inhibitor therapy resulted in a rapid clinical improvement associated with a reduction in inflammatory markers in the first year of the treatment. After 5 years the global retention rate of TNF-α inhibitor was 57. 3%. The mean survival rate in patients with ETA (42.6%) was significantly better than patients treated with INF (23.2%) or ADA (34.1%; p<0.05). The mean duration of therapy was significantly longer for ETA (4.5 years: p<0.05) when compared with ADA (3.25 years p<0.05) or INF (2.5 years: p<0.05). Main reasons for discontinuation were drug adverse events (35 patients: 5 ETA, 15 INF, 15 ADA), and inefficacy (133 patients: 38/85 INF, 61/139 ADA and 34/73 ETA). Conclusions: TNF-α inhibitors constitute an effective therapeutic option for RA patients refractory to disease-modifying anti-rheumatic drugs. In our clinical practice, ETA has significantly higher survival rate over five years when compared with ADA and INF. All anti-TNF demonstrate an acceptable safety profile, but ETA showed lower rates of AEs and inefficiency unlike ADA and INF since the second year of treatment. Their survival rate remains high in the first years of treatment, decreasing considerably after the second year. References: Brennan FM, Maini RN, Feldmann M: TNF-a pivotal role in rheumatoid arthritis Br J Rheumatol 1992; 31: 293-8. Freldmann M, Brenna FM, Malnl RN. Role of cytokines in rheumatoid arthritis Ann Rev Immunol 1996; 14: 397-440 Disclosure of Interest: None Declared